Application of Multiple Regression in Estimating the Amount of Population Growth in Siantar District - Ayu Wulandari; Agus Perdana Windarto; Hendry Qurniawan (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2022)
The purpose of this study is to solve a case or problem that makes decision makers experience various obstacles in estimating the amount of population growth each year by using multiple linear regression algorithms as a solution to solving cases. The data used in this study was obtained directly from the official website of the Central Statistics Agency (BPS) Simalungun in the form of a softcopy book file entitled "Siantar District in Figures 2020" via the url http://simalungun.bps.go.id. with population data from the Siantar District from 2016-2020, there are 17 villages. The data that has been obtained is then processed using Data Mining estimates of the Multiple Linear Regression algorithm and research testing is carried out using the help of Rapid Miner 9.10 Software. By doing this research, research results are obtained that can provide information or input to the government through related agencies to anticipate the number of population growth in Siantar District every year.